MSME Balance Sheet in Strengthening Capacity Building and Trust Access to Capital - Muh Fahrurrozi (Cita konsultindo, 2023)
This study aimed to determine the balance of MSME balances in strengthening capacity building and trust access to capital. The research used in this study was a qualitative approach. The type of this research approach is descriptive. The type of qualitative descriptive research used in this study was intended to obtain information from informants, namely MSMEs in East Lombok Regency, Indonesia, totalling 30 MSMEs. The study results were 1) The financial recording system is carried out manually and is still very simple. The reason for making financial records is to make it easier for owners to give bonuses to their employees, 2) Factors that cause the failure of internal factors in the form of lack of understanding, discipline and human resources.